Gender Difference: The Use of English Discourse Markers in Business News Articles by Vietnamese Journalists - Thao, Tran Quoc; Vinh, Phan Huu (VNU Journal of Science: Education Research; Vol 37 No 4, 2021)
Discourse markers (DMs) appear in a quite high frequency in both spoken and written language. Moreover, they are not only cohesive devices but also tools which help convey language users’ intentions to their discourse. Research into DMs is, nevertheless, still rare regarding the use of English DMs by Vietnamese writers. Therefore, the aim of this study is to examine the use of English DMs in business news articles by Vietnamese male and female journalists. To that end, 80 business news articles written in English by Vietnamese journalists were chosen. Kopple’s (1985) [1], Fung’s (2003) [2], and Fraser’s (1996, 1999) [3-4] theoretical frameworks are adapted for data analysis. It was found that both Vietnamese male and female employed English DMs in their writing in a similar way. Female journalists were, nevertheless, found to employ the interpersonal functions of the used English DMs more than their counterparts.